Flashy lungs and sarcoidosis: not always a sign of disease activity - Lucinian, Yousif A.; Martineau , Patrick; Harel, Francois; Pelletier-Galarneau, Matthieu (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
This is the case of a 68-year-old man with known cardiac sarcoidosis undergoing treatment with methotrexate who presented with new onset of dyspnea and lipothymia. FDG-PET/CT revealed pathological uptake within lung parenchyma which resolved following discontinuation of methotrexate, compatible with methotrexate-induced pneumonitis. This is the first case of methotrexate-induced pneumonitis documented by FDG-PET/CT.